(untitled) - Janasz, Suzanne C. De (Boston, M.A., 2006)
Interpersonal Skills in Organizations, 2nd Edition, by deJanasz, Dowd, and Schneider takes a fresh, thoughtful look at the key skills necessary for personnel and managerial success in organizations today. Chock-full of exercises, cases and group activities, the book employs an experiential approach suitable for all student audiences. The book is broken up into 4 distinct sections (Understanding Yourself, Understanding Others, Understanding Teams, and Leading) that can be used collectively or modularly depending on the instructor's preference and student-audience need.
Keywords: Organizational behavior,Psychology, Industrial,Interpersonal relations